Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-19T22:51:17+01:00
(x⁴-1)÷(x-2) = x³ + 2x² + 4x + 8
-x⁴+2x³
______
2x³ - 1
-2x³+4x²
________
4x² - 1
-4x²+8x
________
8x - 1
-8x +16
_________
15

(x⁴-1)÷(x-2) = x³ + 2x² + 4x + 8 r. 15

Spr. (x - 2)(x³ + 2x² + 4x + 8) + 15 = x⁴ + 2x³ + 4x² + 8x -2x³ - 4x² - 8x - 16 + 15 = x⁴ - 1


(x⁴-1)÷(x-1) = x³ + x² + x +1
-x⁴+x³
_____
x³ - 1
-x²+x²
_______
x² - 1
-x² + x
_________
x - 1
-x + 1
______
= =

(x⁴-1)÷(x-1) = x³ + x² + x +1

Spr. (x-1)(x³ + x² + x +1) = x⁴ + x³ + x² + x - x³ - x² - x - 1 = x⁴ - 1